SITE-SPECIFIC INCORPORATION OF URANYL CARBONATE SPECIES AT THE CALCITE SURFACE - Reeder R.J.; Elzinga E.J.; Tait C.D.; Rector K.D.; Donohoe R.J.; Morris D.E. (My University, 2004)
Spatially resolved luminescence spectra from U(VI) co-precipitated at the (101̄4) growth surface of synthetic calcite single crystals confirm heterogeneous incorporation corresponding to the distribution of structurally non-equivalent steps composing the vicinal surfaces of spiral growth hillocks. Spectral structure from U(VI) luminescence at the “–” vicinal regions and featureless, weak luminescence at the “+” vicinal regions are consistent with previously reported observations of enrichment at the former sites during calcite growth. Luminescence spectra differ between the non-equivalent regions of the crystal, with the spectral features from the “–” vicinal region corresponding to those observed in bulk calcite samples. Subtle spectral shifts are observed from U(VI) co-precipitated with microcrystalline calcite synthesized by a different method, and all of the U(VI)-calcite sample spectra differ significantly from that of U(VI) co-precipitated with aragonite.The step-selective incorporation of U(VI) can be explained by a proposed model in which the allowed orientation for adsorption of the dominant calcium uranyl triscarbonate species is controlled by the atomic arrangement at step edges. Differences in the tilt angles of carbonate groups between non-equivalent growth steps favor adsorption of the calcium uranyl triscarbonate species at “–” steps, as observed in experiments.